Era Baru dalam Ritual Keagamaan: Studi Ziarah Kubur di Masa Pandemi Covid-19: STUDI ZIARAH KUBUR DI MASA PANDEMI COVID-19 - Ahmad Zainuri; Fitriani Fitriani (Tsaqofah, 2021)
Abstract Religious rituals during the COVID-19 pandemic are indeed different from previous times. Nowadays, it is required to use a series of conditions in running it. In various regions in carrying out many worship activities, cultural rites, religion must be limited by several provisions. In celebration, not all will attend the assembly or mosque. As for this article, the author uses a phenomenological approach methodology to map current phenomena on the surface that are different from religious activities before the outbreak of Covid-19. The result of this study is that pilgrimage to the grave has become a rite in Islamic society when approaching major holidays, making pilgrimages always a social gathering and ritual that must be carried out even though there is a pandemic. However, with this pandemic, many public cemeteries have been closed and many appeals not to come to the graves during the pandemic, especially during major holidays in Islam. So it can be concluded that the religious ritual of pilgrimage to the grave, which has taken root in the community and becomes a ritual that must be carried out when approaching a certain day, cannot be limited even with the Covid-19 pandemic. Abstrak Ritual keagamaan di masa pandemi covid-19 ini memang berbeda dengan masa-masa sebelumnya. Masa hari ini dituntut untuk menggunakan serangkaian persyaratan dalam melaksanakannya. Di berbagai daerah dalam melaksanakan banyak kegiatan peribadatan, ritus budaya, agama harus dibatasi dengan beberapa ketentuan. Dalam perayaannya, memang tidak semua akan hadir dalam sebuah majelis atau masjid. Adapun pada artikel ini penulis menggunakan metodologi pendekatan fenomenologi untuk memetakan sebuah kejadian fenomena yang hari ini timbul dipermukaan yang ada sebuah perbedaan dengan kegiatan keagamaan di kala sebelum mewabahnya covid-19. Hasil daripada kajian ini ialah ziarah kubur yang sudah menjadi ritus dalam masyarakat Islam ketika menjelang hari-hari besar, menjadikan ziarah akan selalu menjadi pertemuan dan ritual keagamaan yang tetap harus dikerjakan meski pandemi. Namun, dengan adanya pandemi ini, tempat pemakaman umum banyak yang ditutup dan banyak himbauan untuk tidak datang ke makam di masa-masa pandemi, terutama ketika hari-hari besar dalam Islam. Sehingga dapat disimpulkan bahwa ritual keagamaan ziarah kubur yang sudah mengakar dalam masyarakat dan menjadi ritual yang wajib dikerjakan ketika menjelang hari tertentu, tidak bisa dibatasi meskipun dengan adanya pandemi Covid-19 ini.